Substantia nigra related gene polymorphisms associated with antipsychotic-induced acute movement disorders: a genome-wide association study and multi-ancestry validation in schizophrenia - Zhe Lu; Yao-Yao Sun; Zhe-Wei Kang; Guo-Rui Zhao; Yu-Yanan Zhang; Jun-Yuan Sun; Rui Yuan; Wei-Hua Yue (Military Medical Research)
Abstract Background Antipsychotic-induced movement disorders (AIMDs) are prevalent side effects of antipsychotics, particularly during the acute phase of treatment. This study aimed to elucidate the genetic mechanisms underlying AIMDs using a genome-wide association study (GWAS). Methods GWASs on AIMDs were conducted in 3 independent cohorts: a discovery cohort of 3067 patients (2016 subjects were reserved after quality control), a validation cohort of 277 patients, and a multi-ancestry validation cohort of 766 patients. Subsequent post-GWAS analyses included gene-based analyses, transcriptome-wide association studies (TWASs), and polygenic risk score (PRS) profiling. Results Our study identified 2 loci located in RAB44 gene (rs116249243, P = 5.98 × 10–9; rs117097482, P = 1.17 × 10–8) associated with extrapyramidal symptoms (EPSs), 1 locus (rs6826172, P = 5.56 × 10–9) related to akathisia, and 76 loci linked to involuntary movements (11 genes were mapped). Risk loci located in CNTNAP2, LUZP2, TMEM167A, and RAB44 genes were successfully replicated in the validation cohort, whereas the locus located in RAB44 was also replicated in the multi-ancestry cohort. Gene-based analyses indicated that XRCC4 and PAIP2B reached significance at the genome-wide level in involuntary movements. Tissue expression analysis revealed that involuntary movement-related genes are predominantly expressed in the substantia nigra. Additionally, the TWAS suggested a causal relationship between XRCC4 and involuntary movement. The PRSs derived from the discovery cohort significantly predicted AIMDs in the validation cohort, with area under the receiver operating characteristic curve (AUC) values from 0.60 to 0.80. Conclusions Our findings highlight the role of substantia nigra related gene polymorphisms in AIMDs. This study provides novel insights into the pathogenesis of AIMDs and supports the potential for personalized treatment approaches for schizophrenia. Trial registration ChiCTR ( https://www.chictr.org.cn/showproj.html?proj=8604 ), No. ChiCTR-TRC-10000934; ChiCTR ( https://www.chictr.org.cn/showproj.html?proj=129668 ), No. ChiCTR2100048320.